Investment arithmetic : a practical guide to the methods of financial calculations - Rix, M. S.; Investments - accounting (Great Britain : Pitman Publishing, 1951)
This book is concerned with simple but fundamental investment mathematics and technicalities.
Includes index.
rua 24/05/17
Loans.
Keywords: Investments - mathematics; Business mathematics